Utility of CT Angiography for the Prediction of Coronary Artery Compression in Patients Undergoing Transcatheter Pulmonary Valve Replacement. Issue 3 (May 2020) - Rinaldi, Elizabeth; Sadeghi, Soraya; Rajpal, Saurabh; Boe, Brian A.; Daniels, Curt; Cheatham, John; Sinha, Sanjay; Levi, Daniel S.; Aboulhosn, Jamil
Objectives: We aimed to evaluate the utility of computed tomography angiography (CTA) for coronary compression (CC) prediction in patients with congenital heart disease undergoing balloon-expandable transcatheter pulmonary valve replacement (TPVR). Background: Coronary compression is a serious complication of TPVR, but the value of preprocedural CTAs to assess CC risk is largely unexplored. Methods: In all, 586 patients underwent TPVR between January 2009 and July 2018. Adults with a pre-TPVR CTA and children with a CTA performed less than one year prior to TPVR were included. Patients with poor CTA image quality or with aborted cases due to reasons other than CC were excluded. Sixty-six patients were finally included. Cardiac anatomy was assessed via multiplanar reconstruction of CTAs. Results: Coronary compression occurred in 9 (14%) of the 66 patients who underwent TPVR. Most CC cases (seven of nine) occurred in patients with conduits. Proximity of the right ventricular outflow tract (RVOT) landing zone to the coronary arteries and to the chest wall was a significant risk factor for compression ( P < .001 and P = .019, respectively). Compression risk increased significantly if patients had an RVOT to coronary artery distance of ≤3 mm ( P < .001) and an RVOT to chest wall distance of ≤8 mm ( P = .026). Anomalous course of coronary arteries was another significant univariate risk factor ( P = .003). Conclusions: Right ventricular outflow tract landing zone distance of ≤3 mm to a coronary artery, landing zone distance of ≤8 mm to the chest wall, and anomalous coronary arteries are associated with increased CC risk. Electrocardiogram gating may not be necessary if coronary arteries are opacified on CTAs. Larger studies are needed to explore and confirm these coronary artery compression risk factors.